Necesidad de reformar el art. 129, numeral 2, del Código De La Niñez Y Adolescencia, con la finalidad de que se extienda el derecho de alimentos hasta la profesionalización del alimentante - Criollo Méndez, Moisés Orlando (2015)
The Law of Ecuadorian contains procedures of control for the persons who go out of the country and who the same ones have contracted obligations inside the same one, since he is the case of the food presentations of the children, girls and teen children of emigrants, in consequence it is necessary that parameters of control are established on the part of companies transportations, governmental institutions and international organizations. The Constitution of the Republic of the Ecuador in its article 6 provides: "article 6. Ecuadorians and Ecuadorians are citizens and shall enjoy the rights established in the Constitution." The Ecuadorian nationality is the political persons legal link with the State, without prejudice to their belonging to one of the indigenous nationalities coexisting in the plurinational Ecuador. Ecuadorian nationality by birth or by naturalization is obtained and will not be lost by the marriage or its dissolution, or for the acquisition of another nationality Food and the rights of children should be guaranteed by law, and who are obligated to seek the common good, and above all the right of children and adolescents of Ecuadorian society, so that the rights of the alimentantes and fed should not be therefore violated legal reforms must be within the due process and with respect for the constitutional and legal guarantes. Within the jurisprudential framework there is no sinomia between rights or guarantees if they are established in the Constitution and guaranteed their supremacy or international instruments such as; more when it comes to children and adolescents in the Ecuador; and that their rights must prevail, you must have a short and simple procedure by which justice protects this right without limitations and conditions that put in doubt fabric the rights of adolescents when they are studying until completion of their studies, abiding by the principles of freedom guaranteed in the Constitution